A Self‐Assembled Hetero‐Structured Inverse‐Spinel and Anti‐Perovskite Nanocomposite for Ultrafast Water Oxidation. Issue 31 (29th June 2020) - Ma, Nana; Chen, Gao; Zhu, Yanping; Sun, Hainan; Dai, Jie; Chu, Hang; Ran, Ran; Zhou, Wei; Cai, Rui; Shao, Zongping
Abstract: Spinel and perovskite with distinctive crystal structures are two of the most popular material families in electrocatalysis, which, however, usually show poor conductivity, causing a negative effect on the charge transfer process during electrochemical reactions. Herein, a highly conductive inverse spinel (Fe3 O4 ) and anti‐perovskite (Ni3 FeN) hetero‐structured nanocomposite is reported as a superior oxygen evolution electrocatalyst, which can be facilely prepared based on a one‐pot synthesis strategy. Thanks to the strong hybridization between Ni/Fe 3d and N 2p orbitals, the Ni3 FeN is easily transformed into NiFe (oxy)hydroxide as the real active species during the oxygen evolution reaction (OER) process, while the Fe3 O4 component with low O‐p band center relative to Fermi level is structurally stable. As a result, both high surface reactivity and bulk electronic transport ability are reached. By directly growing Fe3 O4 /Ni3 FeN heterostructure on freestanding carbon fiber paper and testing based on the three‐electrode configuration, it requires only 160 mV overpotential to deliver a current density of 30 mA cm −2 for OER. Also, negligible performance decay is observed within a prolonged test period of 100 h. This work sheds light on the rational design of novel heterostructure materials for electrocatalysis. Abstract : A highly conductive inverse spinel (Fe3 O4 ) and anti‐perovskite (Ni3 FeN) hetero‐structured nanocomposite is facilely synthesized as a superior oxygen evolution electrocatalyst. Both high surface reactivity and bulk electronic transport ability can be realized during the partial reconstruction process. The anti‐structured Fe3 O4 /Ni3 FeN grown on the carbon fiber paper demonstrates a world‐record oxygen evolution reaction performance.